PENDIDIKAN ISLAM BERBASIS LIVING QUR’AN PADA MASYARAKAT ADAT KOTA MASOHI - M. Chusnus Salim Ramadhani; Muhammad Arif Syihabuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the potential for social segregation due to differences in Islamic mass organization (Ormas) affiliations in Indonesia, which often trigger differences in religious practices. In Masohi City, this phenomenon is bridged through the